(untitled) - Adeyeye, Adedamola David

Exploring the dynamics of innovation for inclusive development systems: a study of the Nigerian growth enhancement support scheme (Stellenbosch : Stellenbosch University, 2023)
Thesis (DPhil)--Stellenbosch University, 2022.